Case Report: Efficacy of Ninjin'yoeito Treatment for Idiopathic Pulmonary Fibrosis - Kushima, Hisako; Ishii, Hiroshi; Fujita, Masaki (Frontiers in Nutrition, 2021)
Ninjin’yoeito, a Kampo prescription, was administered to two patients with idiopathic pulmonary fibrosis (IPF) over a period of 12 weeks to improve loss of appetite and lassitude. In Case 1, improvements were observed in appetite, lassitude, and breathlessness, as well as increases or increasing tendencies in body weight, blood albumin level, and hemoglobin (Hb) level. Case 2 showed no changes in appetite but improvements in lassitude and no deterioration of breathlessness. His body weight and his blood albumin and Hb levels increased or showed increasing trends. In both cases, a trend for improvement of respiratory function was observed. In summary, ninjin’yoeito trended to improve the subjective symptoms and nutritional status of a patient with pulmonary fibrosis.